Be polite and kind - Meiners, Cheri J., 1957- (Meiners, Cheri J., 1957- Learning to get along., 2004)
Demonstrates ways of showing politeness, speaking kindly, using basic courtesies, and respecting the feelings of others. Includes role-playing activities.